How firms respond to mandatory information disclosure - Doshi, Anil R.; Dowell, Glen W. S.; Toffel, Michael W. (Strategic Management Journal, 2013)
Mandatory information disclosure regulations seek to create institutional pressure to spur performance improvement. By examining how organizational characteristics moderate establishments' responses to a prominent environmental information disclosure program, we provide among the first empirical evidence characterizing heterogeneous responses by those mandated to disclose information. We find particularly rapid improvement among establishments located close to their headquarters and among establishments with proximate siblings, especially when the proximate siblings are in the same industry. Large establishments improve more slowly than small establishments in sparse regions, but both groups perform similarly in dense regions, suggesting that density mitigates the power of large establishments to resist institutional pressures. Finally, establishments owned by private firms outperform those owned by public firms. We highlight implications for institutional theory, managers, and policymakers . Copyright © 2013 John Wiley & Sons, Ltd.